Odpowiedzi

2010-03-18T19:03:28+01:00
A) ax2-5x-3x2-6x+x2-2x = -13x-2x2+ax2
b) x4+2x2+x+2x3-4x2+3 = x-2x2+2x3+x4+3
Najlepsza Odpowiedź!
2010-03-18T19:15:26+01:00
A)
a x ( x -5 ) -3 ( x² -2x ) + ( x -2 ) = ax² -5ax -3x² -6x +x -2 = ax² -5ax -3x² -5x -2
b)
x ( x² +2x +1 ) - ( -4x³ +8x² -6 ) :2 = x³ +2x² + x + 4x³ -8x² + 6 : 2 = 5x³ -6x² + x + 3
c)
12b * ( b -1 ) :4 + 14 * (b² -2b) :21 - (b -b²) :3 = 12b² - 12b :4 + 14b² - 28b -b + b² : 3 = 12b² - 3b + 14b² - 28b - b + b²/3 = 26b² - 32b + b²/3

Chyba dobrze. @_@ No... mam nadzieję, że pomogłem.
2 5 2